Dinamika Interaksi Santriwati Dengan Al-Qur’an Saat Haid: Studi Kualitatif di Pesantren Tahfidz Maskanul Huffadz - Ali Mahruf; Adek Indra Wiguna; Fairuz Hammurabbi (Publikasi Indonesia, 2025)
This study aims to explore the dynamics of students' interaction with the Qur'an when experiencing menstruation in the context of memorizing the Qur'an at the Maskanul Huffadz Islamic Boarding School. This phenomenon is important to study considering the diverse opinions of scholars regarding the law of reading the Qur'an for menstruating women, as well as its impact on the sustainability of the tahfidz program. This research uses a qualitative approach with an intrinsic type of case study. Data was collected through in-depth interviews, participatory observations, and documentation, and was analyzed thematically. The results of the study show that there are four main categories of understanding among students: (1) total prohibition, (2) conditional ability, (3) contextual approach, and (4) intention-based reading. This difference has direct implications for learning strategies, psychological conditions, and student memorization achievements. In addition, it was found that Islamic boarding schools institutionally provide space for negotiation and adaptation, both through oral policies, moderate guidance approaches, and the provision of learning facilities. This research confirms that women's experiences in Qur'an education not only shape contextual religious practices, but also become the basis for the development of a fiqh approach that is responsive to the biological and pedagogical needs of Muslim women. The main contribution of this research lies in the rereading of the relationship between classical fiqh texts and tahfidz education practices based on the experience of students.